(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study investigated the management of PTSD among teachers in security-challenged areas of Kogi State with the intervention instrumentality of REBT. The study used a randomized control-trial-pretest-posttest design. The researchers recruited 90 teachers from 111 teachers with PTSD that met the inclusion criteria. The National Center 2016 for PTSD Checklist for DSM-5 (PCL-5) was used for data collection. The repeated measures 2-way Analysis of Variance (ANOVA) was the statistical technique used to determine the effect of REBTI on PTSD of teachers. More so, the effect size of REBTI was gotten through Partial eta square and adjusted R2 values. The result revealed that REBT significantly reduced PTSD of teachers than those in the control group. The effect sizes of .937 and .813 at the posttest and follow-up measures indicate that 93.7% and 81.3% decreases in the post-traumatic stress disorder of the experimental group participants are attributed to the effect of REBT intervention. More so, the impact of REBT in the reduction was significantly sustained over a period of time. Based on the findings of this study, the researchers recommended that the school counsellors, and school administrators should employ the services of REBT in reducing teachers’ PTSD in conflict-challenged areas of Kogi State. Teachers with PTSD in conflict-challenged areas can avail themselves of the opportunity of seeking intervention through the principles of REBT since it has been empirically proven to be significant in the reduction of their PTSD.